SISTEM INFORMASI PELAYANAN ADMINISTRASI RUKUN WARGA MENGGUNAKAN METODE WATERFALL - Bobo, Harditias Yonathan; Susanto, Gaguk; Syahminan (Department of System Information, 2024)
Administrative services include various activities such as recording information, correspondence, making financial records, typing documents, and organizing agendas, as well as other tasks related to technical administration. The purpose of this service is to assist residents in managing various aspects of their administration, including making cover letters, making dues payments, recording population data, and supervising various service activities at the community level. This Community Unit Administration Service Information System was built using the codeigniter framework and using the waterfall development model. From the results of the research conducted, it resulted in an application in the form of a Community Unit Administration Service Information System that has been measured for the level of application feasibility by conducting User Acceptance (UAT) testing which obtained very good category results with an average percentage of 89.51% from 3 assessment aspects.